2008
DOI: 10.1111/j.1440-1746.2008.05505.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased melibiose/rhamnose ratio in bile of rats with acute cholestasis

Abstract: The present study is the first to describe in detail pharmacokinetic parameters and the biliary excretion of melibiose and rhamnose in healthy and cholestatic rats. The altered melibiose/rhamnose biliary excretion ratio in BDO rats indicates that the test is able to detect the impairment of the blood-biliary barrier in acute extrahepatic cholestasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…40 As a marker of bloodbiliary barrier permeability, we used the ratio of melibiose/ rhamnose biliary excretion, which sensitively increases during acute cholestasis. 16 Our present data indicate that the blood-biliary barrier becomes further impaired along with the increasing duration of cholestasis. Release of the bile duct obstruction is then associated with a progressive improvement in barrier permeability, which may reflect a decline in intrabiliary pressure.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…40 As a marker of bloodbiliary barrier permeability, we used the ratio of melibiose/ rhamnose biliary excretion, which sensitively increases during acute cholestasis. 16 Our present data indicate that the blood-biliary barrier becomes further impaired along with the increasing duration of cholestasis. Release of the bile duct obstruction is then associated with a progressive improvement in barrier permeability, which may reflect a decline in intrabiliary pressure.…”
Section: Discussionsupporting
confidence: 52%
“…This is associated with a leakage of the solutes from bile to blood and vice versa 40 . As a marker of blood‐biliary barrier permeability, we used the ratio of melibiose/rhamnose biliary excretion, which sensitively increases during acute cholestasis 16 . Our present data indicate that the blood‐biliary barrier becomes further impaired along with the increasing duration of cholestasis.…”
Section: Discussionmentioning
confidence: 71%
“…Its cumulative 24-hour urinary recovery reported in rats and humans was 65% and about 74%, respectively [45,46]. The biliary elimination in rats is negligible [47]. The rest of the applied dose seems to be, at least partially, reduced to rhamnitol [48].…”
Section: Discussionmentioning
confidence: 99%
“…No comprehensive toxicity studies have been carried out about melibiose, but doses up to 5 g have been administered orally to children without reported side effects (38,39). Furthermore, it has been shown that melibiose is not significantly hydrolyzed to monosaccharides after intravenous administration to rats (40) and that it is mostly secreted to urine without metabolization (41). This suggests that melibiose is relatively inert in mammals.…”
Section: Protein Secondary Structure Analysis Using Ft-irmentioning
confidence: 97%